Fundamentals of Bile Duct Injuries From Prevention to Multidisciplinary Management - Pekolj, Juan.; Ardiles, Victoria; Glinka, Juan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Bile duct injuries (BDI) are considered the most serious surgical complication associated with cholecystectomy. According to different reports, its incidence has remained constant over the years, ranging from 0.1% to 0.9%. BDI is associated with a greater risk of perioperative morbidity and mortality, a reduction in the quality of life, and a decrease in long-term survival. Also, this complication is a concern to surgeons since its progression is uncertain and may lead to demands on professional responsibility ("malpractice") and emotional and physical consequences ("second victim"). Given that injuries in a high percentage of patients are initially unsuspected, the postoperative recovery may be prolonged, and the possibility of a successful repair reduced. Several surgical, endoscopic, and percutaneous procedures may be necessary to manage the lesions and to treat coexisting complications. BDI patients often undergo several repair attempts before successful resolution. This affects their quality of life and has a high psychological, physical, and mental impact due to the prolonged, complex, and unexpected nature of the injury. This currently represents a frequent problem in specialized referral centers or hepatobilopancreatic surgery units, where patients arrive with the sequelae of previous inadequate treatments. Usually, these patients require more elaborate procedures such as reoperations, liver resections and liver transplantation. The prevention, early diagnosis, and adequate treatment in the first approach is of crucial importance to ensure good long-term results. Therefore, this book is an essential resource for surgeons who perform cholecystectomy or treat BDI patients. It provides practical information and a comprehensive review on prevention and proper management, including complex cases. Readers will find contributions by experienced authors from a multidisciplinary and reference team in the management of BDI patients.
Chapter 01: Introduction -- Chapter 02: Anatomical Considerations -- Chapter 03: Prevention -- Chapter 04: Essential aspects BDI management -- Chapter 05: Physiopathology of BDI -- Chapter 06: Classification of BDI -- Chapter 07: Intraoperative Diagnosis and Treatment -- Chapter 08: Postoperative diagnosis of BDI$1 (Bs -- Chapter 09: Role of imaging -- Chapter 10: Assessment of vascular structures in BDI$1 (Bs -- Chapter 11: Postoperative Treatment -- Chapter 12: Role of percutaneous procedures -- Chapter 13: Role of Endoscopic Procedures -- Chapter 14: Role of Laparoscopy -- Chapter 15: Biliodigestive Anastomoses -- Chapter 16: Liver Resections -- Chapter 17: Liver Transplantation.s
Keywords: Gastroenterology; Internal medicine; Transplantation of organs, tissues, etc; Surgery; Gastroenterology; Internal Medicine; Transplantation; Surgery; Bile Ducts -- injuries